2022
DOI: 10.3390/ijms232113052
|View full text |Cite
|
Sign up to set email alerts
|

Enriched Environment Attenuates Enhanced Trait Anxiety in Association with Normalization of Aberrant Neuro-Inflammatory Events

Abstract: Neuroinflammation is discussed to play a role in specific subgroups of different psychiatric disorders, including anxiety disorders. We have previously shown that a mouse model of trait anxiety (HAB) displays enhanced microglial density and phagocytic activity in key regions of anxiety circuits compared to normal-anxiety controls (NAB). Using minocycline, we provided causal evidence that reducing microglial activation within the dentate gyrus (DG) attenuated enhanced anxiety in HABs. Besides pharmacological in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 67 publications
2
1
0
Order By: Relevance
“…We know that MS increases hippocampal neuroplasticity [ 26 , 27 ] and neurogenesis [ 28 , 29 ], but we did not address this process in the present study. It is also known that MS decreases neuroinflammation [ 30 , 31 ], and our data support this important role of MS. We showed that there was a decrease in the expression of GFAP, a marker for astrocyte activation, in the HC of Adrβ 3 KO and WT mice after the 8-week MS protocol. Iba-1, a marker for microglia activation, was also reduced in Adrβ 3 KO mice exposed to the MS protocol.…”
Section: Discussionsupporting
confidence: 88%
“…We know that MS increases hippocampal neuroplasticity [ 26 , 27 ] and neurogenesis [ 28 , 29 ], but we did not address this process in the present study. It is also known that MS decreases neuroinflammation [ 30 , 31 ], and our data support this important role of MS. We showed that there was a decrease in the expression of GFAP, a marker for astrocyte activation, in the HC of Adrβ 3 KO and WT mice after the 8-week MS protocol. Iba-1, a marker for microglia activation, was also reduced in Adrβ 3 KO mice exposed to the MS protocol.…”
Section: Discussionsupporting
confidence: 88%
“…We know that MS increases hippocampal neuroplasticity [34,35] and neurogenesis [36,37], but we did not address this process in the present study. It is also known that MS decreases neuroinflammation [38,39], and our data gives support to this important role of MS. We showed that there is a decrease in the expression of GFAP, a marker for astrocyte activation, in the HC of Adrβ3KO and WT mice after the 8-week MS protocol. Iba-1, a marker for microglia activation, was also reduced in Adrβ3KO exposed to the MS protocol Mounting evidences indicates a close relationship between glial cells in both cognitive impairments [40,41], and in the pathogenesis of neurodegenerative disorder, such as Alzheimer's disease [42,43].…”
Section: Discussionsupporting
confidence: 85%
“…In various animal models, EE has been shown to alter a range of inflammatory mechanisms, exerting anti-inflammatory or inhibitory effects on microglial “activation” ( 75 ). Some studies have indicated that EE can reduce inflammation and oxidative stress in the brain ( 76 ).…”
Section: Resultsmentioning
confidence: 99%